1994
DOI: 10.1002/ijc.2910580314
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast activation protein: Purification, epitope mapping and induction by growth factors

Abstract: The human fibroblast activation protein (FAP) defined by monoclonal antibody (MAb) F19 is a cell surface antigen expressed in reactive stromal fibroblasts of breast, colorectal, lung and other epithelial cancers. In contrast to its stroma-specific localization in epithelial neoplasms, FAP is expressed in the malignant mesenchymal cells of bone and soft tissue sarcomas. FAP is transiently expressed in some fetal mesenchymal tissues but is absent or expressed at low levels in most adult tissues. FAP is induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 19 publications
4
82
0
1
Order By: Relevance
“…Our experiments demonstrate that FAP expression slows growth and decreases the threshold for cell death under stress conditions. FAP is not expressed in resting epidermal melanocytes but is upregulated when these cells are activated to proliferate (Rettig et al, 1993). Consistent with these observations, common melanocytic nevi, which are hyperplastic lesions of melanocytes, express FAP (Huber et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Our experiments demonstrate that FAP expression slows growth and decreases the threshold for cell death under stress conditions. FAP is not expressed in resting epidermal melanocytes but is upregulated when these cells are activated to proliferate (Rettig et al, 1993). Consistent with these observations, common melanocytic nevi, which are hyperplastic lesions of melanocytes, express FAP (Huber et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…Immunohistochemical analysis of human skin lesions showed that FAP is present in a proportion of melanocytic nevi and absent from both primary and metastatic melanoma lesions (Huber et al, 2003). FAP expression in human melanocytes is abrogated when they undergo malignant transformation and acquire tumorigenic potential and growth factor independence (Rettig et al, 1993). Overall, these observations reveal that FAP is lost during malignant transformation of proliferating melanocytes, suggesting that its expression may abrogate tumorigenicity.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations